Labor force heterogeneity and wage polarization: Italy and Spain. Issue 5 (8th October 2018) - Addabbo, Tindara; García-Fernández, Rosa María; Llorca-Rodríguez, Carmen María; Maccagnan, Anna
Abstract : Purpose: The purpose of this paper is to assess the change in the Italian and Spanish wage polarization degree in a time of economic crisis, taking into account the factors affecting labor force heterogeneity. Gender differences in the evolution of social fractures are considered by carrying out the analysis separately for males and females. Design/methodology/approach: The approach by Palacios-Gonzánlez and García-Fernández (2012) on polarization is applied to the microdata provided by the EU Living Conditions Surveys (2007, 2010 and 2012). According to Palacios-Gonzánlez and García-Fernández's approach, polarization is generated by two tendencies that contribute to the generation of social tension: the homogeneity or cohesion within group and the heterogeneity between groups. The following labor force characteristics are considered: gender, level of education, type of contract, occupational status and job status. Findings: The results for Italy reveal a higher increase of polarization for women than for men from the perspective of the type of contract. In Spain, the wage polarization of women also increases more intensively compared to men from the perspectives of level of education, job status and occupational status, while in Italy the reduction of the wage polarization index by level of education can be related, above all, to an increase in overqualification of women. Originality/value: While the empirical literature on polarization has made considerable investigation into employment and job polarization, this paper explores the rather less explored matter of wage polarization. Furthermore, particular attention is paid to the impact on polarization of the Great Recession.